ANALYSIS OF THE EFFECTS OF PRODUCT QUALITY, PROMOTION & LOCATION ON LOYALTY USING SATISFACTION AS THE MEDIATING VARIABLE AT LOTTEMART OF TAMAN SURYA JAKARTA - Ruth Wulandari, Dyah; Ngadino Surip (Dinasti Publisher, 2020)
This study aims to know and analyze the influences of product quality, promotion and location on the customer loyalty either directly or through the customer satisfaction as the mediator variable and also to know and analyze the influence of customer satisfaction on the customer loyalty at hypermarket Lottemart of Taman Surya. Data collection is conducted through questionnaire. Sample used in this study consists of 400 respondents of customers of hypermarket Lottemart of Taman Surya Jakarta. The sampling technique in this research uses non probability sampling technique. The method of analysis used is Partial Least Square (PLS) assisted with SmartPLS application. The results of the research reveal that quality product, promotion and location have a positive and significant effect on customer satisfaction. Product quality, promotion and customer satisfaction have a positive and significant effect on customer loyalty but location has no significant effect on customer loyalty.